757 Does Increased Sampling of Cerebrospinal Fluid from External Ventricular Drains Lead to Increased Rates of Infection?. (4th May 2021) - Edwards, B; Zolnourian, A; Bulters, D
Abstract: Introduction: External ventricular drains (EVDs) are commonly used in the management of acute hydrocephalus after subarachnoid haemorrhage (SAH). Infection is the most common complication. There remains controversy over whether frequent sampling is associated with increased risk of infection. Method: Two cohorts of patients requiring EVD after SAH were retrospectively analysed for suspected and proven CSF infection. The first clinical cohort was of 50 consecutive patients with twice weekly sampling. The second group had alternate daily sampling as part of a prospective research study. Results: Female to male ratio were (32:18) and (29:15) in clinical vs research group respectively. Average age of both groups was 59. Average length of treatment with EVD in both groups was 10 days. 16/50 (32%) patients had a suspected infection vs 13/44 (30%) and 8/50 (16%) had a proven infection compared to 6/44 (14%) in clinical and research groups, respectively. There was no statistically significant difference between the two groups (suspected infections p = 0.7 and proven infections p = 0.7) Conclusions: Increased rates in CSF sampling in the research cohort did not result in higher rates of CSF infection. This suggests that rate of sampling, if done following a strict protocol, is not associated with increased risk of infection.